2023
DOI: 10.1093/nar/gkad032
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human HelQ with DNA polymerase delta halts DNA synthesis and stimulates DNA single-strand annealing

Abstract: DNA strand breaks are repaired by DNA synthesis from an exposed DNA end paired with a homologous DNA template. DNA polymerase delta (Pol δ) catalyses DNA synthesis in multiple eukaryotic DNA break repair pathways but triggers genome instability unless its activity is restrained. We show that human HelQ halts DNA synthesis by isolated Pol δ and Pol δ-PCNA-RPA holoenzyme. Using novel HelQ mutant proteins we identify that inhibition of Pol δ is independent of DNA binding, and maps to a 70 amino acid intrinsically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Recent studies have shown that HELQ interacts with the POLD3 subunit of the DNA replicative polymerase Polο to suppress DNA synthesis during break-induced replication (BIR) and promote DNA strand annealing (He et al, 2023). We thought to investigate if loss of POLD3 has a similar impact as HELQ on ssDNA gap accumulation in PRIMPOL-overexpressing cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown that HELQ interacts with the POLD3 subunit of the DNA replicative polymerase Polο to suppress DNA synthesis during break-induced replication (BIR) and promote DNA strand annealing (He et al, 2023). We thought to investigate if loss of POLD3 has a similar impact as HELQ on ssDNA gap accumulation in PRIMPOL-overexpressing cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that BRCA-deficient cells accumulate gaps upon treatment with cisplatin and other replication stress-inducing agents, and this may correlate with their chemosensitivity (Cong et al, 2021a;Hale et al, 2023;Panzarino et al, 2021;Quinet et al, 2021;Quinet et al, 2020;Tirman et al, 2021). The surprising gap suppression effect observed upon RAD52 depletion in PRIMPOL-overexpressing cells prompted us to investigate if a similar effect occurs in BRCA-deficient cells.…”
Section: Rad52 Promotes Ssdna Gap Accumulation In Primpol-overexpress...mentioning
confidence: 95%
See 3 more Smart Citations